Immunoglobulin-like transcript 2 as an impaired anti-tumor cytotoxicity marker of natural killer cells in patients with hepatocellular carcinoma - Sakata, Toshihiro; Yoshio, Sachiyo; Yamazoe, Taiji; Mori, Taizo; Kakazu, Eiji; Aoki, Yoshihiko; Aoyanagi, Nobuyoshi; Okamoto, Toru; Ito, Takanori; Toyoda, Hidenori; Kawaguchi, Takumi; Ono, Yoshihiro; et al. (Frontiers in Immunology, 2024)
Introduction Natural killer (NK) cells play a pivotal role in immune surveillance in the liver. We aimed to identify potential targets for NK cell-mediated immune intervention by revealing the functional molecules on NK cells in HCC patients. Methods To evaluate the impact of aging on NK cell phenotypes, we examined NK cells from healthy volunteers (HVs) of various ages. Because ILT2 expression on CD56dim NK cells increased with increasing age, we enrolled age-matched HCC patients and HVs. We determined the NK cell phenotypes in blood mononuclear cells (PBMCs) and intrahepatic lymphocytes (IHLs) from cancerous and non-cancerous tissues. We evaluated cytotoxicity and antibody-dependent cellular cytotoxicity (ADCC) of NK cells in vitro. Results ILT2-positive CD56dim NK cells in PBMCs were increased in HCC patients compared with HVs. In HCC patients, ILT2-positive CD56dim NK cells were increased in cancerous IHLs compared with non-cancerous IHLs and PBMCs. We examined the impact of macrophage migration inhibitory factor (MIF) on ILT2 expression in co-cultures of HCC cells and NK cells. The enhanced expression of ILT2 on CD56dim NK cells from HCC patients was inhibited by masking antibodies against MIF and CXCR4. ILT2-positive CD56dim NK cells exhibited lower capacities for cytotoxicity and ADCC than ILT2-negative cells, which were partially restored by ILT2 blockade. Conclusions In HCC patients, ILT2 is a signature molecule for cancerous CD56dim NK cells with impaired cytolytic capacity. The MIF-CXCR4 interaction is associated with ILT2 induction on CD56dim NK cells and ILT2 serves as a target for functional NK cell restoration.